THE PATHOPHYSIOLOGY RELATIONSHIP OF THE DEVELOPMENT OF CORONAVIRUS DISEASE, PERIODONTAL DISEASES AND DIABETES MELLITUS BASED ON ANALYSIS OF MODERN LITERATURE SOURCES - O.O. Bugerchuk; M.M. Rozhko; T.I. Matviykiv; O.V. Bugerchuk (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2022)
At the end of 2019, the SARS-CoV-2 virus pandemic swept the world, forcing billions of people to learn to live in a world full of new rules and restrictions. From the beginning of the pandemic, doctors learned to fight this virus, and later - to study and fight the consequences and complications of this disease. It is known that most infected people, especially at a young age, have a milder course of the disease compared to older people. In some patients, the disease progresses rapidly and various complications develop. . Therefore, early detection and timely treatment of critical cases is very important. The purpose of the study was to analyze the pathophysiological relationship between COVID-19, diabetes mellitus and periodontal tissue diseases, based on the experience of foreign specialists according to a review of modern literary sources. Key words: COVID-19, diabetes mellitus, periodontitis, ACE-2.